Comparison of in-vitro falloposcopy with tubal histology in the diagnosis of Fallopian tube pathology - Rimbach, Stefan; Wallwiener, Diethelm; Barth, C.; Heberling, Dirk; Bastert, Gunther (Human reproduction, 1996)
In order to assess the diagnostic quality of falloposcopy in relation to pathomorphology, a consecutive series of 30 Fallopian tubes obtained from surgical salpingectomy cases were prospectively examined by in-vitro falloposcopy and histology. Falloposcopy was performed using an over-the-wire catheterization system and a 0.5 mm falloposcope with 3000 pixels. Assessment of the specimens included the description of lumen geometry, intraluminal changes and status of the mucosal surface. Falloposcopy classified 14 tubes as normal and 16 pathological. Histology resulted in 17 normal versus 13 pathological tubes. Pathologies included lumen obstructions and dilatations, intraluminal synechiae and mucosal damage. Sensitivity and specificity of falloposcopy were calculated to be 0.85 and 0.71; positive and negative predictive values were 0.69 and 0.86. It was concluded that falloposcopic findings indeed reflect and successfully differentiate normal and pathological conditions allowing adequate and reproducible image interpretation. However, variations of the diagnostic accuracy with the type of pathology and the tubal segment have to be taken into account before clinical consequences are drawn from a falloposcopic investigation.
Gesehen am 28.02.2024